Herzfrequenzvariabilität (HRV) und subjektives Belastungsempfinden (PE) während spielsportspezifischer Ausdauerbelastung - Gerhard, J.; Lott, C.; Hoos, O. (Herzfrequenzvariabilität: Gesundheitsförderung - Trainingssteuerung - Biofeedback. Internationales Symposium am 29. und 30. Oktober., 2011)
Nonlinear measures of heart rate variability as well as measures of perceived exertion (PE) are able to detect subtle changes from moderate to high intensity exercise. Additionally, both approaches are associated with complex models of cardio-vascular regulation and exercise fatigue. Nevertheless, a direct link between HRV and perceived exertion is still lacking and further research for intermittent high intensity exercise is scarce. Therefore, this study evaluates the dynamics of HRV-and PE-parameters during an intermittent game-specific endurance test. 23 healthy active men and women (age: 23,3 ± 6,4 y) performed a modified Yo-Yo intermittent recovery test level 1 (YoYofRlmod) until exhaustion. RR-Intervals were measured betöre, during and affer YoYo/R1mod and PE was assessed using a 7 point scale. Beneath traditional HRV parameters, fractal correlation properties and predictability of RR-intervals were analysed using short-term scaling exponent a1 of DFA and sample entropy (SampEn). A repeated measure ANOVA was used to reveal significant changes in HRV-parameters with increasing PE. Furthermore Pearson correlations were calculated between HRV-parameters and PE. With increasing exercise intensity, nonlinear HRV-parameter a1 strongly decreases (p < 0,01) while SampEn significantly increases (p < 0,01), whereas linear parameters remamed fairly constant. Strong correlations could be revealed between PE and a1 (r = -0,76; p < 0,01) and SampEn (r = 0,70; p < 0,01). respectively.